2010
DOI: 10.1017/s0031182010001149
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the liver fluke, Fasciola hepatica: the effect of time and spatial separation on the genetic diversity of fluke populations in the Netherlands

Abstract: An evaluation of the genetic diversity within Fasciola hepatica (liver fluke) may provide an insight into its potential to respond to environmental changes, such as anthelmintic use or climate change. In this study, we determined the mitochondrial DNA haplotypes of > 400 flukes from 29 individual cattle, from 2 farms in the Netherlands, as an exemplar of fasciolosis in a European context. Analysis of this dataset has provided us with a measure of the genetic variation within infrapopulations (individual hosts)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 30 publications
0
43
1
Order By: Relevance
“…Notably, European F. hepatica populations showed extensive genetic mtDNA diversity even in local studies (Ireland and the Netherlands) [37,38]. Partial sequences of mitochondrial genes nad1 and cox1 revealed 4.1 and 2.3% sequence variation, respectively, in flukes sampled across Eastern Europe [40].…”
Section: Low Genetic Diversity and Pronounced Star-like Haplotype Netmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, European F. hepatica populations showed extensive genetic mtDNA diversity even in local studies (Ireland and the Netherlands) [37,38]. Partial sequences of mitochondrial genes nad1 and cox1 revealed 4.1 and 2.3% sequence variation, respectively, in flukes sampled across Eastern Europe [40].…”
Section: Low Genetic Diversity and Pronounced Star-like Haplotype Netmentioning
confidence: 99%
“…Over the past few years, many efforts focused on studying the population genetic structure and heterogeneity of important trematode species including Schistosoma mansoni [25][26][27][28][29][30], S. japonicum [31][32][33], Paragonimus westermani [34,35], Fasciola hepatica [36][37][38][39][40], F. magnum [41] Echinostoma sp. [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The most valuable and most common mitochondrial genes were presented in Section 3.1.2. Only three studies Walker et al, 2011;Kantzoura et al, 2011) concerned different but found to be most polymorphic fragments from mtDNA of F. hepatica (consisted from partial cox3 (cytochrome c oxidase 3) gene, tRNA-His, partial cob (cytochrome B) gene). Again predominance of the researches refers to single geographic isolates of F. hepatica but not forming a worldwide picture of populational groups' distribution.…”
Section: Mtdna Gene Regions Analysismentioning
confidence: 99%
“…Choosing "plastic"fragments of liver fluke mitochondrion means choosing the most informative and adequate markers for obtaining a complete view on genetic diversity of F. hepatica in the world. Nevertheless only three available in bibliographic data bases studies could give such a picture (Semyenova et al, 2006;Teofanova et al, 2011;Walker et al, 2011). One of them is genetic diversity investigation of liver fluke populations from Eastern Europe .…”
Section: Mtdna Gene Regions Analysismentioning
confidence: 99%
“…In this context, Ollerenshaw and Rowlands (1959) were the first researchers to develop a prediction model for the incidence of Fasciola hepatica based on meteorological data. Since that time, several studies using modeling to predict the incidence F. hepatica have been conducted to develop a system for predicting the disease in space and time (HOPE-CAWDERY et al, 1981;DE WAAL et al, 2007;KENYON et al, 2009;MAS-COMA et al, 2009;MCCANN et al, 2010;FOX et al, 2011;WALKER et al, 2011;FOX et al, 2012).…”
Section: Introductionmentioning
confidence: 99%